A Single Common Assay for Robust and Rapid Fragile X Mental Retardation Syndrome Screening From Dried Blood Spots - Tan, Vivienne J.; Lian, Mulias; Faradz, Sultana M.H.; Winarni, Tri I.; Chong, Samuel S. (Frontiers in Genetics, 2018)
Background:FMR1 CGG trinucleotide repeat hyper-expansions are observed in 99% of individuals with fragile X mental retardation syndrome (FXS). We evaluated the reliability of a rapid single-step gender-neutral molecular screen for FXS when performed on DNA isolated from dried blood spots. Methods: DNA was extracted from dried blood spots of 151 individuals with intellectual disability or autism spectrum disorder, whose FMR1 repeat genotypes are known. Dried blood spots were blinded prior to DNA extraction and analysis by triplet primed PCR (TP-PCR) and melt curve analysis (MCA). All expansion-positive and representative expansion-negative samples were also genotyped by fluorescent TP-PCR and capillary electrophoresis (CE) to confirm repeat expansion status. Results: Three males and 12 females were classified as expanded by TP-PCR MCA, and were subsequently sized by fluorescent TP-PCR CE. Two males and four females carried premutations, while one male and eight females carried full mutations. All 19 non-expanded samples that were sized were confirmed as carrying only normal alleles. Replicate analysis of representative expansion-positive samples yielded reproducible melt peak profiles. TP-PCR MCA classifications were completely concordant with FMR1 CGG repeat genotypes. Conclusion: TP-PCR MCA of dried blood spot DNA accurately and reliably identifies presence/absence of FMR1 CGG repeat expansions in both genders simultaneously. This strategy may be suitable for rapid high-throughput first-tier screening for fragile X syndrome.